Новый вид рода Bembecia (Lepidoptera, Sesiidae) из Талыша - Горбунов, О.Г. (Вестник зоологии, 1987)
B. zuvandica Go r bu n o v, sp. n. is described. Type - Io ca Ii t y: Azerbaijan SSR, Talysh Mts., Zuvand, 1100-15000 m. Ho st p l ants: Onobrychis cornuta (L.) De s v., 0. hohenackeriana C. A. Me y, Melilotus officibalis (L.) Pa 11. Type mater i a I - holotype, paratypes 19, 15 - is deposited in the Zoological Institute, USSR Academy of Sciences, Leningrad (including holotype), Zoological Museum, Moscow State University, Zoological Museum, Kiev State University, Institute of Animal Morphology and Ecology, USSR Academy of Sciences, Moscow, coll. Dr. Z. Lastuvka (CSSR, Brno).